Distracción ósea mandibular: Presentación de un caso Osteomandibular distraction: A case report - Anselmo López Rodríguez; Angel Soto Fernández; Herminia Pérez Varela; Delfina Pantoja Valdés (Editorial Ciencias Médicas, 2004)
Se muestra el avance obtenido en la técnica de distracción ósea en el Hospital Clínicoquirúrgico "Manuel Fajardo" mediante la presentación de un caso. Se analiza esta experiencia tomando como patrón los trabajos de los Dres. Chender, Molina y Guerrero, los cuales han contribuido y colaborado en la aplicación y desarrollo de esta novedosa técnica de elongación ósea. El paciente atendido por este método padecía de retrucción mandibular y en él se utilizó la fijación maxilo-mandibular después de retirado el distractor para garantizar la formación del callo óseo. Se señala que Ortiz Monasterio y Molina, en una serie de 106 casos, no observaron recidivas en su seguimiento de 3 años. The osteogenic distraction is a method used for bone lengthening by applying a distraction apparatus. Described and used by Dr. Codevilla in the first years (1905) of the XX century, this method was later (1950) developed by Dr. Llizarov in the field of Orthopedics and Traumatology. In the specialty of Maxillofacial Surgery, It became something very novel for the correction of the maxillomandibular development abnormalities, since according to what is estipulated the bone will be lengthened from 1 to 2 mm daily, so the correction of a mandibular retrusion of 15 mm will take between 7 and 15 days, according to the times the distractor's rod is turned. The advance attained with this technique at "Comandante Manuel Fajardo" Clinical and Surgical Hospital is shown through the report of a case, and this experience is analyzed taking as a reference the work done by Dr. Chender, Dr. Molina and Dr. Guerrero, who have contributed to and collaborated with the application and development of this new technique of bone lengthening. The patient treated by this method suffered from mandibular retrusion. In this patient, the maxillomandibular fixation was used after removing the distractor to guarantee the formation of the bony callus. It was stressed that Ortiz Monasterio and Molina did not observe relapses in a series of 106 cases in a 3-year follow-up.